Optimization of the process for separating ethylene glycol and 1,2-butanediol using reactive distillation-assisted separation based on a parallel stochastic algorithm framework - Kong, Jie; Liu, Wenshuo; Fu, Yu; Zhang, Xin; Li, Yuanxin; Li, Jun; Sun, Lanyi (Separation and purification technology, 2025)
The process of separating ethylene glycol and 1,2-butanediol with reactive distillation is intricate, with many variables involved, leading to a time-consuming and inefficient optimization process. To expedite the optimization process, this study proposes a new parallel stochastic algorithm framework. This research shows that the framework is 36.8 times faster than the serial framework. The reactive distillation-assisted separation process of ethylene glycol and 1,2-butanediol is optimized using the parallel stochastic algorithm framework. The optimization process duration is 810 min. Based on the optimal design, the process is further intensified by incorporating the dividing wall column and intermediate reboiler. Compared to the base process, the intensified process exhibited reductions of 8.89 %, 10.18 %, and 9.83 % in total capital cost, total operating cost, and total annual cost, respectively.